KUALITAS PESAN GURU MATEMATIKA SMP NEGERI 1 MEULABOH DALAM KOMUNIKASI PEMBELAJARAN MATEMATIKA - Jamal, Fakhrul; Jerba, Hasprianti; Maisuri, Maisuri (Genta Mulia : Jurnal Ilmiah Pendidikan, 2021)
Abstrak: This study aims to investigate the choice of message design logic by the mathematics teacher at SMP Negeri 1 Meulaboh. This study was designed to gain information and understanding about the way mathematics teachers think when they construct verbal messages to their students. The subjects of this study were 4 mathematics teachers who taught in Negeri 1 Meulaboh. This research was conducted in November 2020. Data collection was carried out by means of observation and interviews. Based on the results of the research and discussion above, it can be concluded that the mathematics teachers at SMP Negeri 1 Meulaboh are good at communication styles, this can be seen from the four teachers studied, three of whom have used rhetorical communication styles. Rhetorical message design, because this communication style is easier for children to accept and understand when absorbing math material.Â Kata kunci: Komunikasi, Ekspresif, Konvensional, Retorikal, Matematika.